Evaluation of the Color Stability of Three Resin-Ceramic Materials Using a Spectrophotometer and a Digital Photography Software - Nicolas Naffah; Hani Ounsi; Mutlu Ozcan; Ziad Salameh (Wolters Kluwer Medknow Publications, 2024)
Background: Computer-aided design/computer-aided manufacturing (CAD/CAM) resin ceramics allow easier milling than glass ceramics but are suspected to be more stainable. Although Photoshop® is widely used for picture analysis, its potential for shade selection has not been properly assessed. Aim: Purpose primary: To evaluate the color stability of three CAD/CAM resin ceramics and Lithium Disilicate. Secondary: to compare the color evaluation between a spectrophotometer (Vita Easyshade compact) and Photoshop software. Materials and Methods: Three CAD/CAM resin ceramic materials (n = 10) and a fourth group of lithium disilicate were used. Half of each group were thermocycled (5°C and 55°C; 3000 cycles). All samples were immersed in colored beverages (coffee, tea and red wine) for 30 days. Values were obtained by spectrophotometry and photographs analyzed using Photoshop software. The parameters measured were CIEL*a*b, and the color difference (ΔE) was analyzed. A mixed model test was used to compare the results through time and materials (α = 0.05). The comparison between the spectrophotometer and Photoshop results was performed using the bivariate Pearson's correlation test. Results: Lithium disilicate glass ceramic exhibited less color change (ΔE = 14) than resin ceramics (15.7 < ΔE < 18.7). The least change was noted with GC Cerasmart (ΔE = 15.7) followed by Vita Enamic (ΔE = 17*) and Brilliant Crios (ΔE = 18.7*). Spectrophotometer and Photoshop values showed low correlations. Conclusions: Resin ceramics may suffer from color change in clinical use. Photoshop is technique sensitive; pictures are easily affected by the light conditions and camera settings.